Supervillin associates with androgen receptor and modulates its transcriptional activity - Ting, Huei-Ju (The National Academy of Sciences, 2002)
Activation of androgen receptor (AR) via androgen in muscle cells has been closely linked to their growth and differentiation. Here, we report the cloning and characterization of supervillin (SV), a 205-kDa actin-binding protein, as an AR coregulator from the skeletal muscle cDNA library. Mammalian two-hybrid and glutathione S-transferase pull-down assays indicate a domain within SV (amino acids 594-1268) can interact with AR N terminus and DNA-binding domain–ligand-binding domain in a ligand-enhanced manner. Subcellular colocalization studies with fluorescence staining indicate SV can colocalize with AR in the presence of 5α-dihydrotestosterone in COS-1 cells. The functional reporter assays showed full-length SV and the SV peptide (amino acids 831-1281) within the interaction domain can enhance AR transactivation. Furthermore, SV can enhance the endogenous AR target gene, p27(KIP1), expression in prostate PC-3(AR2) cells. SV preferentially enhanced AR rather than other tested nuclear receptors and could be induced by natural androgens better than other steroids. SV can also cooperate with other AR coregulators, such as ARA55 or ARA70, to enhance AR transactivation further. Unlike SRC-1 that can enhance the interaction between AR N terminus and AR C terminus, SV shows a mild suppressive effect on N–C interactions, suggesting SV may go through a different mechanism to enhance AR transactivation. Together, our data demonstrate that SV is an AR coregulator that can enhance AR transactivation in muscle and other cells.